2021
DOI: 10.1021/acsomega.1c03444
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Half-Metallicity in Monolayer MoSi2N4

Abstract: First-principles calculations are performed for the recently synthesized monolayer MoSi2N4 [Science 369, 670–674 (2020)]. We show that N vacancies are energetically favorable over Si vacancies, except for Fermi energies close to the conduction band edge in the N-rich environment, and induce half-metallicity. N and Si vacancies generate magnetic moments of 1.0 and 2.0 μB, respectively, with potential applications in spintronics. We also demonstrate that N and Si vacancies can be used to effectively engineer the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…26,27 Recently, 2D TMN MoSi 2 N 4 and WSi 2 N 4 have been experimentally fabricated 28 and quickly gained intense interest in the scientific community. [29][30][31] MoSi 2 N 4 (and also WSi 2 N 4 ) has a seven atomic layer structure with a MoN 2 (WN 2 ) monolayer sandwiched between two Si 2 N 2 monolayers. Here, MoN 2 has the same structure as MoS 2 while Si 2 N 2 has the InS-type of structure.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Recently, 2D TMN MoSi 2 N 4 and WSi 2 N 4 have been experimentally fabricated 28 and quickly gained intense interest in the scientific community. [29][30][31] MoSi 2 N 4 (and also WSi 2 N 4 ) has a seven atomic layer structure with a MoN 2 (WN 2 ) monolayer sandwiched between two Si 2 N 2 monolayers. Here, MoN 2 has the same structure as MoS 2 while Si 2 N 2 has the InS-type of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Mortazavi et al 27 showed that 2D MoSi 2 N 4 material exhibits outstanding piezoelectricity and stiffness with outstanding capabilities in photocatalytic applications. Beyond the pristine monolayer form, the physical properties of 2D MoSi 2 N 4 material can be further modulated by the external conditions, including doping, 28−30 strain engineering, 31,32 and atomic vacancies, 34 thus revealing the exceptional material design flexibility of this emerging 2D material family. More interestingly, the vertically stacked van der Waals (vdW) heterostructure (HTS) is considered an effective approach to modulate the features and to extend the possibility of applications of 2D materials.…”
mentioning
confidence: 99%
“…Mortazavi et al showed that 2D MoSi 2 N 4 material exhibits outstanding piezoelectricity and stiffness with outstanding capabilities in photocatalytic applications. Beyond the pristine monolayer form, the physical properties of 2D MoSi 2 N 4 material can be further modulated by the external conditions, including doping, strain engineering, , stacking layers, and atomic vacancies, thus revealing the exceptional material design flexibility of this emerging 2D material family.…”
mentioning
confidence: 99%
“…Therefore, V Si and V N vacancies are comparatively the most likely vacancies to appear, as the more probable structure holds low formation energy. 19,20 It is proved in ref. 20 that V N is the most likely vacancy to appear in the structure, followed by the V Si .…”
Section: Resultsmentioning
confidence: 86%